The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acs.jpcc.0c00156
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Pyrrolidinium-Based Ionic Liquids under Confinement. I. Analysis of Dielectric Permittivity

Abstract: Dielectric spectroscopy of geometrically confined ionic liquids is an effective approach to study how finite size and interfacial effects modify the conductivity behavior. An ideal geometry for such experiments are pores or channels that run parallel to the electric field lines, as in this case, no Maxwell–Wagner-type effect is assumed to interfere with a straightforward data analysis. However, the permittivity of such channels in anodized alumina membranes filled with the ionic liquid shows the hallmark of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…This can be done according to the procedure described elsewhere. 69 In previous works, we have demonstrated that the alumina template oneself and incomplete filling of the nanopores (filling degree ∼90%) do not affect the position of the α-peak and spectral shape for embedded glass-forming liquids and polymers (it only shifts ε″ toward higher values depending on the porosity). 70 , 71 However, in our case, the degree of filling of the nanochannels with the tested polymer was—at least for those AAO membranes with larger pore sizes—much beyond that.…”
Section: Methodsmentioning
confidence: 82%
“…This can be done according to the procedure described elsewhere. 69 In previous works, we have demonstrated that the alumina template oneself and incomplete filling of the nanopores (filling degree ∼90%) do not affect the position of the α-peak and spectral shape for embedded glass-forming liquids and polymers (it only shifts ε″ toward higher values depending on the porosity). 70 , 71 However, in our case, the degree of filling of the nanochannels with the tested polymer was—at least for those AAO membranes with larger pore sizes—much beyond that.…”
Section: Methodsmentioning
confidence: 82%
“…In such a case, it is impossible to avid air-gaps inside the nanochannels, and additional corrections for some insulating blockage within the pore are needed. This can be done according to the procedure described in our recent paper . However, assuming that the nanopores are filled with PMPS 2.5k, only up to 90%, we also expect no shift of the α-peak and spectral broadening (see Figure , “pure polymer, porosity, and air gaps corrections”).…”
Section: Methodsmentioning
confidence: 96%
“…This can be done according to the procedure described in our recent paper. 69 If we assume that the nanopores are filled with PMPS 2.5k only up to 90%, we can also expect no shift of the α-peak, and spectral broadening (see Figure 7, "pure polymer, porosity, and air gap corrections").…”
Section: ■ Methodsmentioning
confidence: 98%
“…Because the electric field runs along the nanopore channels, the entire heterogeneous dielectric response problem can be modeled using the equivalent circuit composed of the two capacitors connected in parallel. In such a case, the dielectric permittivity of a composite material (the raw data that we measure using an impedance analyzer) is the sum of the dielectric permittivity of the individual componentsconfined polymer and alumina matrixweighted by the respective volume fractions where φ is the porosity of the alumina membrane, ε AAO is the dielectric permittivity of the alumina membrane, and ε polymer is the dielectric permittivity of the confined polymer. Thus, for the real and imaginary parts, we get …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation